Understanding the Role of the Environmental Arena and Community Social Structure in Stunting Prevention Education: Memahami Peran Arena Lingkungan dan Struktur Sosial Masyarakat dalam Pendidikan Pencegahan Stunting - Nyoman Suwarta; Dwi Astutiek; Edi Dwi Riyanto; Ahmad Nurefendi Fradana; Joko Susilo; Yulia Mega Puspita (Universitas Muhammadiyah Sidoarjo, 2023)
Indonesia is a country with the third highest incidence of stunting in Southeast Asia. Stunting has various negative impacts therefore it is important to prevent it through public education. This research aims to understand the role of the environmental arena and social structure of society in stunting prevention education. This research uses a qualitative method with a case study approach. The research analysis explains the problem of stunting through four environmental arenas and social structures that exist in communities in four cities or districts, including the educational, economic, cultural, and ideological arenas. By understanding the roots of the stunting problem identified through the environmental arena and social structure of society, we can identify effective methods for stunting prevention programs in the field, namely sustainable education based on local culture in all aspects of community life. Highlights : Interconnected Factors: The research explores how various environmental arenas and social structures intertwine to contribute to the prevalence of stunting. Local Cultural Context: Understanding the local cultural context is crucial for designing effective stunting prevention education programs. Sustainability and Community Engagement: Emphasizing sustainable education initiatives rooted in local culture ensures long-term engagement and effectiveness in combating stunting. Keywords : arena, education, economy, culture, ideology